2021
DOI: 10.1101/2021.04.12.21255308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of vaccination with CoronaVac in a cohort of healthcare workers (HCW) - preliminary report

Abstract: Background: CoronaVac, a vaccine containing inactivated SARS-CoV-2, demonstrated efficacy of 50.39% 14 days or more after the 2nd dose. The objective of this study is to report the occurrence of symptomatic COVID-19 in a cohort of HCW vaccinated with CoronaVac and to estimate its effectiveness. Methods: CoronaVac was given to HCWs in Hospital das Clinicas on 18-21 January, 2021 (epi week 3) (22,402 HCWs), and on 14-16 February, 2021 (epi week 7) (21,652 HCWs). Weekly cases of symptomatic COVID-19 were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 10 publications
(8 reference statements)
4
26
0
1
Order By: Relevance
“…For the Alpha variant, ChAdOx1 (University of Oxford-AstraZeneca), BNT162b2 (Pfizer-BioNTech) and Ad26.COV2.S (Janssen Pharmaceuticals) vaccines showed a slight effectiveness reduction, with 70%, 90% and 80% of protection, respectively [98][99][100]. For the Gamma variant, CoronaVac (Sinovac Research and Development) and Ad26.COV2.S (Janssen Pharmaceuticals) vaccines did not show significant reduction in protection [98,101]. Finally, concerning the Delta variant, it was shown that BNT162b2 (Pfizer-BioNTech) and mRNA-1273 (Moderna) vaccines did not elicit antibody neutralization responses against this variant, which demonstrated 6.8 times more resistance to neutralization [102].…”
Section: Immune Response Induced By Covid-19 Vaccinesmentioning
confidence: 99%
“…For the Alpha variant, ChAdOx1 (University of Oxford-AstraZeneca), BNT162b2 (Pfizer-BioNTech) and Ad26.COV2.S (Janssen Pharmaceuticals) vaccines showed a slight effectiveness reduction, with 70%, 90% and 80% of protection, respectively [98][99][100]. For the Gamma variant, CoronaVac (Sinovac Research and Development) and Ad26.COV2.S (Janssen Pharmaceuticals) vaccines did not show significant reduction in protection [98,101]. Finally, concerning the Delta variant, it was shown that BNT162b2 (Pfizer-BioNTech) and mRNA-1273 (Moderna) vaccines did not elicit antibody neutralization responses against this variant, which demonstrated 6.8 times more resistance to neutralization [102].…”
Section: Immune Response Induced By Covid-19 Vaccinesmentioning
confidence: 99%
“…The estimated effectiveness was of 50.7% and 51.8% at two and three weeks after the second dose, respectively. Genomic sequencing of 142 samples found that 47% of the SARS-CoV-2 variants of concern (VOCs) were mostly gamma ( 7 ). However, the severity of confirmed COVID-19 cases was not considered, and the study was conducted before the gamma variant peaked in São Paulo.…”
mentioning
confidence: 99%
“…31 However, these trials were conducted prior to the emergence of the Gamma variant. 31 Several preliminary studies have assessed the effectiveness of CoronaVac in other populations, including elderly individuals in São Paulo State, 32 HCWs in a single centre in São Paulo, 33 elderly age groups in Brazil, 34 and the general population in Chile. 31 More evidence is needed from observational studies conducted in Brazil and other countries where the Gamma variant or other lineages are circulating.…”
Section: Discussionmentioning
confidence: 99%